Current Addiction in Youth: Online Sports Betting - Aragay, Núria; Pijuan, Laia; Cabestany, Àngela; Ramos-Grille, Irene; Garrido, Gemma; Vallès, Vicenç; Jovell-Fernández, Esther (Frontiers in Psychiatry, 2021)
Background: Gambling landscape has changed in recent years with the emergence of online gambling (OG). Greater accessibility and availability of this betting modality can increase the risk of developing a gambling disorder (GD). Online sports betting (OSB) is currently the most common type of OG, but little is known about the clinical characteristics of OSB compared to slot-machine (SM) gamblers, the most common offline gambling disorder. Methods: This was a prospective study conducted between October 2005 and September 2019, and included outpatients diagnosed with GD seen in a Pathological Gambling and Behavioral Addictions referral unit. Only patients with OSB and SM disorders were included. The main objective was to assess the clinical profile of OSB compared to SM gamblers, and to define clinical predictors for developing OSB gambling disorder. Logistic regression was performed to determine the effects of variables on the likelihood of this disorder. Results: Among 1,186 patients attended in our Unit during the study period, 873 patients were included; 32(3.7%) were OSB gamblers and 841 (96.3%) were SM gamblers. Overall, mean age was 45±13 years and 94.3% were men. Compared to SM patients, OSB patients were younger (34.9±9.5 vs 45.3±13), more frequently single (43.8% vs 20.6%) and had a university education level (43.8% vs 4.5%); they were also more frequently non-smokers (18.7% vs 66.7%) and had fewer psychiatric comorbidities (12.5% vs 29.4%) than SM gamblers. GD duration before treatment initiation was shorter in OSB patients than in SM gamblers, most of them (81.3% vs 42.4%) with ≤5 years of GD duration. OSB gamblers showed significant differences in weekly gambling expenditure, spending higher amounts than SM patients. Younger age (OR: 0.919; 95% CI: 0.874-0.966), university education level (OR: 10.658; 95% CI: 3.330-34.119), weekly expenditure >100€ (OR: 5.811; 95% CI:1.544-21.869) and being a non-smoker (OR:13.248; 95% CI:4.332-40.517) were associated with an increased likelihood of OSB gambling behavior. Conclusions: We identified different profiles for OSB and SM gamblers. Younger age, university education level, higher weekly expenditure and non-smoking habit were associated with OSB compared to SM disorders. Prevention strategies should help young people become aware of the severe risks of OSB